Nuclear Matter Without Electrons: The Magneto-Nuclear Periodic Table (MNPT) and the Taxonomy of Nucleomorphs - Barack Ndenga (Publisher, 2025)
I introduce the Magneto-Nuclear Periodic Table (MNPT), a pedagogical and predictive framework for electron-free nuclear matter (here termed nucleomorphs). In this regime, electrons are absent by design and stability is governed by nuclear composition and magnetic confinement rather than by electronic shells. The MNPT organizes hypothetical and semi-physical species into families driven by magnetic moment, spin alignment, and confinement topology. I formulate a Magneto-Nuclear Stability Index that combines magnetic, structural, and mass-to-charge terms to score the plausibility of a nucleomorph under given fields. The framework yields a finite initial table (34 entries) to teach the concept and guide computation and lab trials. I document predicted applications (energy, shielding, quantum memory, propulsion) and provide synthetic routes (natural extraction or laboratory formation). An extended Appendix defines requested symbols (BKP, BKH, NDS, NDL, ART, ARG, ARN… including coded states like ART(3 0 6 0)), giving each a meaning, proposed use, and proposed method of obtaining. This work is hypothesis-driven; experimental confirmation is an open challenge.
This work introduces the Magneto-Nuclear Periodic Table (MNPT), a novel theoretical framework that redefines the organization of matter at the nuclear scale, independent of electron configurations. By focusing on nuclear matter without electrons, MNPT establishes a systematic taxonomy of nucleomorphs, elementary nuclear entities characterized by their magneto-nuclear properties. The MNPT provides: A new periodic classification beyond the electronic periodic table of Mendeleev. Insights into nuclear stability, magnetic interactions, and structural symmetries. A theoretical bridge between nuclear physics, quantum field theory, and condensed matter. A foundation for exploring exotic forms of matter and potential cosmological applications. This first presentation of the MNPT highlights its conceptual and methodological significance, offering researchers an alternative paradigm for investigating nuclear matter, its interactions, and its role in the fundamental architecture of the universe.